2012
DOI: 10.1016/j.coal.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of geological and hydrodynamic controls on methane emissions experienced in a Lower Kittanning coal mine

Abstract: This paper presents a study assessing potential factors and migration paths of methane emissions experienced in a room-and-pillar mine in Lower Kittanning coal, Indiana County, Pennsylvania. Methane emissions were not excessive at idle mining areas, but significant methane was measured during coal mining and loading. Although methane concentrations in the mine did not exceed 1% limit during operation due to the presence of adequate dilution airflow, the source of methane and its migration into the mine was sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For this work, sequential Gaussian co-simulation with Markov-model-1 (MM1) was selected. The absence of need to generate cross-correlation, while still maintaining the ability to produce realistic results [29,41], is an advantage of this method in the face of especially limited data points.…”
Section: Sequential Gaussian Co-simulations Of Primary Variables Withmentioning
confidence: 99%
“…For this work, sequential Gaussian co-simulation with Markov-model-1 (MM1) was selected. The absence of need to generate cross-correlation, while still maintaining the ability to produce realistic results [29,41], is an advantage of this method in the face of especially limited data points.…”
Section: Sequential Gaussian Co-simulations Of Primary Variables Withmentioning
confidence: 99%
“…Gas content generally rises where conventional and hydrodynamic trapping of coal gases arise and may fall in areas of active recharge with downward flow potential and/or convergent flow where there is no mechanism for entrapment (Scott, 2002;Karacan and Goodman, 2012).…”
Section: ) Hydraulic Conditionmentioning
confidence: 99%
“…Volumetric GIP calculation is given in Saulsberry et al (1996) and has been demonstrated by using available coal reservoir data and for various circumstances (Karacan and Goodman, 2012; Karacan et al, 2012; Karacan and Olea, in review). In this work, the 2010 values of the coal reservoir properties spatially shown in Fig.…”
Section: Reservoir Properties Effective Gas Flow Capacity and Gipmentioning
confidence: 99%
“…Heriawan and Koike, 2008; Olea et al, 2011a; Karacan et al, 2012; Karacan and Goodman, 2012; Olea and Luppens, 2012; Karacan and Olea, in review). Most recently, a special issue of International Journal of Coal Geology compiled papers by the leading experts working in coal and geostatistics on applications of geostatistical techniques to coal science, coal geology and related sciences (Olea, 2013).…”
Section: Geostatistical Modeling Of In-seam Methane Drainage and Imentioning
confidence: 99%